Effect of television adverts on children's purchase behaviour: Evidence from Ghana - Bylon Abeeku Bamfo; Jerry Jay Kraa; Perdita Asabere; Bede Akorige Atarah (Cogent Business & Management, 2019)
The study assessed the effect of television advertising on children's purchasing behaviour in Ghana. The population comprised of children between the ages of 13 and 18 years who watched television adverts. The study was conducted on a sample of 230 respondents of which 202 responses, representing 87.83% response rate were received and useable. Data were collected using questionnaire. Convenience and purposive sampling techniques were adopted in selecting respondents. The data were analyzed using IBM Statistical Packages for Social Sciences with the use of multiple linear regressions. The study found quality information, information intrusiveness and likable adverts having positive and significant impacts on children purchase behaviour. The study recommends provision of quality, accurate, reliable, and timely information about products as well as employing popular and likable celebrities in the television advertisement.
Keywords: 650; Advertising; consumer buying behaviour; children; Ghana